Trying a product virtually before buying: examining the role of flow in the consumer purchase intentions - Ratih Siswanina Putri; Imam Salehudin (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Augmented Reality (AR) allows consumers to try products, including make-up, on their faces digitally and in real-time, giving rise to a “try the product before buying” experience when shopping online. The main purpose of this research is to know the advantages of implementing AR based on flow theory. This study analyzes the relationship between interactivity, novelty, vividness, flow, learning, information utility, enjoyment, satisfaction, brand attitude, and purchase intentions in online shopping experiences that apply AR technology. The research has been conducted utilizing an online survey of 229 respondents who have used a smartphone application with AR technology. Using the structural equation modelling (SEM) method, hypothesis testing was carried out using Lisrel 8.8 software. The results showed that AR characteristics such as interactivity and novelty could increase flow, but vividness could not. The results also show that flow can affect increasing learning, information utility, and enjoyment. The results show that the application of AR technology can increase satisfaction, brand attitude, and purchase intentions of application users. On the other hand, the increase in purchase intentions is only influenced by flow and brand attitude in the online shopping experience using AR technology.